Intercultural Communication Interaction of Multicultural Society in West Kalimantan Province: Ethnographic Studies - Fannia, Theresi; Johana, Kornelia; Awliya, Firda; Rismawaty, Fitria; Ameri, Maya; Lianto Lau, Sherly (KnE Social Sciences, 2023)
Indonesia has a society with various cultures, due to which there are many ethnic groups with their respective cultural structures and living side by side, which is called multicultural. West Kalimantan Province is one of the regions in Indonesia where multicultural societies live side by side, known as TIDAYU, namely the Tionghua or Chinese, Dayaknese and Melayu or Malays, which are the three largest tribes in West Kalimantan and divided in various places in West Kalimantan. In fact, one of the cities in West Kalimantan, namely Singkawang City was rewarded as the number one most tolerant city in 2018 based on the assessment of the SETARA Institute in collaboration with the Indonesian Ministry of Home Affairs and the Pancasila Ideology Development Agency, and was again ranked number one in 2021. Based on the research results using ethnology-based qualitative method, people in West Kalimantan have been accustomed to cultural diversity from an early age; therefore, the life of the multicultural society in West Kalimantan has a high level of tolerance and intercultural communication in West Kalimantan runs in harmony and respects each other. Keywords: intercultural communication, interaction, multicultural society, tolerance